Hubungan Antara Motivasi Suami Pada Ibu Hamil Dengan Kunjungan Antenatal Care (ANC) Di Desa Japanan Kecamatan Kemlagi Kabupaten Mojokerto - Mardiyana, Rina; Ayu Anggraini, Diah (JURNAL KEPERAWATAN SEHAT, 2015)
Antenatal Care (ANC) is surveillance before the dressing especially aimed at the growth and development of fetus in the womb. ANC orderly do pregnant women one of which is influenced by motivation husband doing such close contact with the mother in ANC. This is consistent with concept of readiness husband expected at each visit ANC, the husband and wife often accompany his wife to know the condition of pregnancy. Phenomena that exist today are found pregnant women who don’t ANC accompanied by her husband. The purpose of research is the correlation between husband motivation to pregnant women with visits ANC in Japanan Village Kemlagi Mojokerto. Analytic study design is cross-sectional approach. Population that is all pregnant women’s husbands in Japanan Village Kemlagi Mojokerto of 46 people in 2013 and with purposive sampling technique obtained 42 husbands as sample. Data was collected and observations kuisioner KIA books were analyzed using frequency distributions. Then, to determine the relationship of husband motivation to visit ANC by using Chi Square test. The results showed that there is correlation between husband motivation to pregnant women with visits ANC on the ρ (0,00) < (0,05). The results showed that still found pregnant women who don’t ANC, be hoped husband always give motivation to pregnant women so that visits ANC.Keywords:Husband motivation, visits Antenatal Care (ANC)